RELATIONSHIP OF OCCUPATIONAL SAFETY AND HEALTH KNOWLEDGE WITH OSH BEHAVIOR IN LIGHT VEHICLE ENGINEERING DEPARTMENT OF STUDENTS OF SMK N 1 TUMPAAN - Regina Lembong; Parsaoran Tamba; Hendro Sumual (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
The purpose of this study is to determine the relationship between K3 knowledge and OSH behavior by students of the Light Vehicle Engineering Department of Smk N 1 Tumpaan. The method used is a quantitative method with a correlational approach, assisted by the IBM SPSS version 22 analysis tool. The sample in this study amounted to 32 students. The results of this study indicate that there is a strong relationship between K3 knowledge and K3 behavior when practicing light vehicles with a large relationship of (r) = 0.683, K3 knowledge mastered by students must be improved, because there are still students who get the medium category, students' OSH behavior needs to be improved. maintained by the way the teacher must monitor continuously so that students continue to be disciplined in applying K3 principles during work